Targeting B7-H1 (PD-L1) sensitizes cancer cells to chemotherapy. Issue 12 (December 2018) - Wu, Xiaosheng; Li, Yanli; Liu, Xin; Chen, Chunhua; Harrington, Susan M.; Cao, Siyu; Xie, Tiancheng; Pham, Tu; Mansfield, Aaron S.; Yan, Yiyi; Kwon, Eugene D.; Wang, Liewei; et al.
Abstract: Development of resistance to chemotherapy is a major obstacle in extending the survival of patients with cancer. Although originally defined as an immune checkpoint molecule, B7-H1 (also named as PD-L1 or CD274) was found to play a role in cancer chemoresistance; however, the underlying mechanism of action of B7-H1 in regulation of chemotherapy sensitivity remains unclear in cancer cells. Here we show that development of chemoresistance depends on an increased activation of ERK in cancer cells overexpressing B7-H1. Conversely, B7-H1 knockout (KO) by CRISPR/Cas9 renders human cancer cells susceptible to chemotherapy in a cell-context dependent manner through a reduced activation of p38 MAPK. B7-H1 was found to associate with the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) and this association promoted or maintained the activation of ERK or p38 MAPK in cancer cells. Importantly, we found that targeting B7-H1 by anti-B7-H1 monoclonal antibody (H1A) increased the sensitivity of human triple negative breast cancer cells to cisplatin therapy in vivo. Our results suggest that targeting B7-H1 by an antibody capable of disrupting B7-H1 signals may be a new approach to sensitize cancer cells to chemotherapy.